Preparation method of magnesium or magnesium alloy material
By using organic electrolyte on the surface of the conductive metal working electrode for electroplating and deposition, the problem of high preparation cost and low yield of magnesium or magnesium alloy foil is solved, and low cost and high efficiency preparation of magnesium or magnesium alloy materials is achieved.
Patent Information
- Application Number
- CN202411417145.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The prior art is difficult to effectively prepare magnesium or magnesium alloy foils with uniform thickness, and the processing cost is high and the yield is low.
Conductive metal is used as the working electrode, magnesium or magnesium alloy is used as the reference electrode and counter electrode, and electroplating is used to deposit with organic electrolyte including magnesium ions, adjusting the current density, temperature and electrode spacing to control the deposition process.
Magnesium or magnesium alloy materials are prepared at low cost and low power consumption, reducing processing costs, improving yield, and obtaining magnesium or magnesium alloy materials with uniform thickness and uniformity.
Smart Images

Figure CN119506988A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal material preparation, and in particular to a method for preparing magnesium or magnesium alloy material. Background Art
[0002] In the past 20 years, the research and development and application of magnesium and magnesium alloys have achieved rapid development, especially cast magnesium alloy products, which have been widely used in the fields of automobiles, military industry, etc. Rechargeable magnesium battery is a new type of battery with great potential. It has a large theoretical volume capacity (3833 mAh / cm 3 ), rich in resources (lithium content in the earth's crust is about 10 4 The advantages of magnesium alloys such as low reduction potential (-2.37V) and low dendrite growth have attracted wide attention. However, the development of deformed magnesium alloys is relatively slow, especially the development of magnesium alloy sheets and foils mainly produced by rolling is extremely slow.
[0003] The processing of magnesium and magnesium alloy sheets or foils is currently also done by rolling, and is still in the small-batch trial production stage. The thinnest thickness that can be rolled can reach about 30 microns, but it is difficult to roll thinner foils. This is mainly because magnesium is a close-packed hexagonal crystal, with a small number of slip systems that can be started at room temperature, and it is easy to form a very strong basal texture during rolling, resulting in extremely poor plasticity and formability of magnesium, resulting in low deformation per rolling pass, and its rolling production process is longer than that of other metal foils such as aluminum and copper. In addition, the yield rate of magnesium and magnesium alloy sheets is low, and the processing cost is high; the yield rate of magnesium and magnesium alloy foils is even lower, and the processing cost is extremely high.
[0004] Electrolysis is another method for producing metal foil, mainly used for the preparation of copper foil. Electrolytic copper foil is widely used as negative electrode current collector for printed circuit boards and lithium-ion batteries. Electrolytic magnesium is an industrial production method for raw magnesium. It is to electrolyze molten anhydrous magnesium chloride to reduce magnesium ions at the cathode to generate metallic magnesium. The electrolysis temperature is about 700°C. The reduced magnesium floats on the surface of the electrolyte in liquid form. Therefore, magnesium foil cannot be prepared by traditional electrolysis of molten magnesium chloride. The electrode potential of magnesium is lower than that of hydrogen, so it is impossible to obtain magnesium foil by electrolyzing magnesium ions in an aqueous solution system like electrolytic copper foil. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing magnesium or magnesium alloy material, which has a simple process flow, low cost and can produce plate-shaped magnesium or magnesium alloy material with uniform thickness.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing magnesium or magnesium alloy material comprises: using a conductive metal as a working electrode, using magnesium or magnesium alloy as a reference electrode and a counter electrode, immersing the working electrode, the reference electrode and the counter electrode in an organic electrolyte containing magnesium ions, and electroplating and depositing the magnesium or magnesium alloy material on the surface of the working electrode.
[0007] Furthermore, the process parameters of electroplating deposition include: current density is set to 2~100mA / cm 2 , the temperature of the organic electrolyte including magnesium ions is set to 0~85℃, and the electroplating deposition time is set to 0.01~10h.
[0008] Furthermore, the distance between the working electrode and the counter electrode was set to 5-15 mm.
[0009] Furthermore, after the electroplating deposition is completed, the working electrode is immersed in a solvent of an organic electrolyte to remove impurities on the surface of the working electrode.
[0010] Further, the working electrode, the reference electrode and the counter electrode are pretreated before being immersed in the organic electrolyte including magnesium ions; The pretreatment includes: grinding, cleaning, polishing, scrubbing and drying the electrodes, namely the working electrode, the reference electrode and the counter electrode, in sequence to remove impurities on the surfaces of the electrodes.
[0011] Furthermore, the conductive metal includes molybdenum, titanium, stainless steel or copper.
[0012] Furthermore, the organic electrolyte is an ether electrolyte or an ester electrolyte.
[0013] Furthermore, the reference electrode and the counter electrode are pure magnesium, magnesium-lithium alloy or magnesium-gadolinium alloy.
[0014] The present invention has the following unexpected beneficial effects: the present invention is based on the charging principle of magnesium secondary battery and the working principle of magnesium copper half-cell, with conductive metal as the working electrode, magnesium or magnesium alloy as the reference electrode and the counter electrode, the electrolyte is an organic electrolyte including magnesium ions, during electrolysis, the magnesium or magnesium alloy of the counter electrode loses electrons and is oxidized into magnesium ions and enters the electrolyte, the magnesium ions obtain electrons at the working electrode and are reduced to magnesium and deposited on the surface of the working electrode, and magnesium or magnesium alloy materials are obtained as the reduced magnesium nucleates and grows on the working electrode, and the magnesium ions in the electrolytic magnesium or magnesium alloy material are a one-way transmission process from the counter electrode to the working electrode through the electrolyte. The present invention greatly reduces the cost of the preparation process of magnesium or magnesium alloy. When electrolyzed in an organic system electrolyte, the deposition potential is less than 1 V. Combined with industrial practice, the calculation shows that the power consumption of electrolytic magnesium or magnesium alloy is 2200 degrees / ton, and low-cost preparation is achieved. The preparation method has the advantages of environmental friendliness, low cost, and simple preparation process. The obtained magnesium or magnesium alloy material has a small and uniform thickness and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The microscopic morphology of the magnesium foil prepared in Example 1 of the present invention at different magnifications; Figure 2 is an EDS image of the magnesium foil prepared in Example 1 of the present invention; Figure 3 It is the microscopic morphology of magnesium foil deposited at different current densities; Figure 4 It is the microscopic morphology of magnesium foil deposited at different temperatures; Figure 5 It is the microscopic morphology of magnesium foil deposited at different electrode spacings; Figure 6 This is the deposition curve of working electrodes of different materials at different current densities. Figure 7 The working electrodes of different materials are sealed at a current of 2 mA / cm 2 、1mAh / cm 2 The first cycle of deposition dissolution curve during deposition; Figure 8 It is the half-cell curve diagram of working electrodes of different materials; Fig. 9 It is a polarization curve diagram deposited on working electrodes of different materials. DETAILED DESCRIPTION
[0016] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0017] In one embodiment, the present invention provides a method for preparing magnesium or magnesium alloy material, which comprises: using a conductive metal as a working electrode, and using magnesium or magnesium alloy as a reference electrode and a counter electrode, immersing the working electrode, the reference electrode and the counter electrode in an organic electrolyte including magnesium ions, and electroplating and depositing the magnesium or magnesium alloy material on the surface of the working electrode.
[0018] The present invention is based on the principle of electrochemical deposition, that is, under the action of an electric field, magnesium ions in the electrolyte obtain electrons on the surface of the working electrode (cathode) and are reduced to metal atoms, and then deposited to form magnesium or magnesium alloy materials.
[0019] Conductive metal is used as the working electrode (cathode), while magnesium or magnesium alloy is used as the reference electrode and counter electrode (anode). This configuration ensures the stable flow of current during the electrolysis process and is conducive to the reduction and deposition of magnesium ions.
[0020] An organic electrolyte containing magnesium ions is used. Compared with traditional aqueous solutions, the organic electrolyte has higher electrochemical stability and a wider voltage window, which is conducive to electroplating deposition under milder conditions while reducing corrosion to the electrode material.
[0021] The preparation of magnesium or magnesium alloy material specifically includes the following steps: Step 1, electrode preparation: Select and prepare a conductive metal as the working electrode, ensuring that its surface is clean, flat and has good conductivity. At the same time, prepare magnesium or magnesium alloy as the reference electrode and counter electrode.
[0022] Step 2: electrolyte preparation: according to the experimental requirements, prepare an organic electrolyte containing an appropriate amount of magnesium ions.
[0023] Step 3, electrolytic deposition: immerse the working electrode, reference electrode and counter electrode in the electrolyte and apply appropriate voltage or current. Under the action of the electric field, the magnesium ions in the electrolyte migrate to the surface of the working electrode and deposit into magnesium or magnesium alloy material.
[0024] Step 4, post-processing: After the electroplating deposition is completed, the magnesium or magnesium alloy material on the surface of the working electrode is subjected to necessary post-processing, such as cleaning, drying, cutting, etc., to obtain the desired magnesium or magnesium alloy material product.
[0025] The electrochemical deposition method can directly deposit magnesium or magnesium alloy materials on the surface of the conductive metal, i.e. the working electrode, without going through a complicated processing process, thus improving production efficiency. And by adjusting the composition of the electrolyte, electrolysis conditions and other parameters, the thickness, uniformity and quality of the magnesium or magnesium alloy materials can be accurately controlled. The prepared magnesium or magnesium alloy materials have excellent conductivity, ductility and corrosion resistance, and can be widely used in the fields of battery negative electrode materials, electromagnetic shielding materials, packaging materials, etc.
[0026] In summary, the method for preparing magnesium or magnesium alloy materials provided by the present invention has the advantages of simple operation, high efficiency, strong controllability, etc., and provides new ideas and technical means for the preparation and application of magnesium or magnesium alloy materials.
[0027] In a preferred embodiment, the reference electrode and the counter electrode are pure magnesium, magnesium-lithium alloy or magnesium-gadolinium alloy.
[0028] In a preferred embodiment, the process parameters of the electroplating deposition include: the current density is set to 2-30 mA / cm 2 , the temperature of the organic electrolyte including magnesium ions is set to 0~85℃, and the electroplating deposition time is set to 0.01~10h.
[0029] Current density is a key factor in controlling the deposition rate during the electroplating process. A lower current density is conducive to obtaining a denser and more uniform magnesium or magnesium alloy material, but the deposition rate is slower; a higher current density can speed up the deposition rate, but may lead to increased surface roughness of the magnesium or magnesium alloy material, and even defects such as scorching and coarse crystallization. In actual operation, the appropriate current density should be selected according to the required thickness, quality and production efficiency of the magnesium or magnesium alloy material. Usually, it is necessary to determine the optimal current density range through experiments. Preferably, the current density is set to 10mA / cm 2 .
[0030] The electrolyte temperature has a significant effect on the diffusion rate of magnesium ions, the conductivity of the electrolyte, and the kinetics of the electrode reaction. Higher temperatures can increase the conductivity of the electrolyte and the diffusion rate of magnesium ions, thereby accelerating the deposition rate; but too high a temperature may cause the electrolyte to volatilize too quickly, reduce stability, and even induce side reactions. Selecting an appropriate electrolyte temperature is crucial to ensuring the stability of the electroplating process and the quality of deposition. Generally, electroplating at higher temperatures can achieve faster deposition rates, but it is necessary to pay attention to controlling the upper temperature limit to avoid adverse consequences. Preferably, the temperature of the organic electrolyte including magnesium ions is set to 35°C.
[0031] The electroplating deposition time directly determines the thickness of the magnesium or magnesium alloy material. A shorter deposition time may not result in a magnesium or magnesium alloy material of sufficient thickness, while a too long deposition time may result in the magnesium or magnesium alloy material being too thick, increasing internal stress, or even peeling or cracking. The appropriate deposition time is set according to the required magnesium or magnesium alloy material thickness and electroplating efficiency. In actual operation, the deposition process can be monitored by regularly measuring the thickness of the magnesium or magnesium alloy material and making adjustments as needed.
[0032] In summary, the process parameter setting of electroplating deposition needs to comprehensively consider multiple factors such as current density, electrolyte temperature and electroplating deposition time. By optimizing these parameters, high-quality and uniform magnesium or magnesium alloy material products can be obtained. At the same time, it is also necessary to pay attention to controlling other conditions in the electroplating process, such as the stirring speed of the electrolyte, pH stability, electrode spacing, etc., to ensure the smooth progress of the electroplating process and the stability and reliability of the deposition quality.
[0033] In a preferred embodiment, the spacing between the working electrode and the counter electrode is set to 5-15 mm. When the spacing between the working electrode and the counter electrode is small, the electric field strength is relatively high, which helps to accelerate the migration and reduction process of magnesium ions to the surface of the working electrode, thereby increasing the rate of electroplating deposition. However, too small a spacing may also cause the resistance of the electrolyte to decrease, causing part of the electrical energy to be lost in the form of heat energy, thereby reducing energy efficiency. Larger spacing reduces the electric field strength, slows down the migration and reduction rate of magnesium ions, and then reduces the rate of electroplating deposition. However, appropriately increasing the spacing helps to reduce the ohmic drop of the electrolyte, improves the uniformity of current distribution, and reduces the coating quality problems caused by local overheating.
[0034] Appropriate spacing helps ensure uniform distribution of the electric field on the surface of the working electrode, thereby promoting uniform deposition of magnesium ions and obtaining more uniform and dense magnesium or magnesium alloy materials. Too small a spacing may make it difficult to discharge bubbles in the electrolyte, increasing the risk of defects such as pinholes and pitting in the coating. Appropriate spacing helps the escape of bubbles and the circulation and renewal of the electrolyte, reducing the generation of defects.
[0035] Therefore, when setting the spacing between the working electrode and the counter electrode, multiple factors such as electroplating efficiency, coating quality, and ease of operation need to be considered comprehensively. A spacing range of 5 to 15 mm is a relatively reasonable choice, but the specific value also needs to be adjusted and optimized according to the specific electroplating conditions, electrolyte formula, and the required magnesium or magnesium alloy material properties. Further preferably, the spacing between the working electrode and the counter electrode is set to 10 mm.
[0036] In addition, it is also important to note that the stability and consistency of the electrode spacing should be maintained during the electroplating process to avoid fluctuations in electroplating quality due to spacing changes. At the same time, attention should also be paid to the cleaning and maintenance of the electrodes to ensure that their surface flatness and conductivity meet the electroplating requirements.
[0037] In a preferred embodiment, after the electroplating deposition is completed, the working electrode is immersed in a solvent of an organic electrolyte to remove impurities on the surface of the working electrode.
[0038] Since the electroplating process is carried out in an organic electrolyte, it is reasonable to choose the solvent of this electrolyte as the soaking solvent. This ensures good compatibility between the solvent and the residue on the electrode surface, which is conducive to the dissolution and removal of impurities.
[0039] During the soaking process, the solvent can penetrate and dissolve impurities attached to the electrode surface, such as magnesium particles that are not firmly deposited, residues of electrolyte additives, etc. If these impurities are not removed in time, they may affect the purity, conductivity, corrosion resistance and other properties of magnesium or magnesium alloy materials. Soaking also helps to clean the electrode surface, remove defects such as bubbles and microcracks generated during the electroplating process, and make the electrode surface flatter and smoother. This is of great significance for improving the uniformity and appearance quality of magnesium or magnesium alloy materials. During the electroplating process, due to the rapid deposition of magnesium ions, certain internal stress may be generated inside the electrode. The soaking process helps to relieve this internal stress and reduce problems such as cracking and peeling of magnesium or magnesium alloy materials caused by excessive internal stress.
[0040] The soaking time should be determined according to the actual situation. Generally, it is necessary to ensure sufficient time to remove impurities, but it is also necessary to avoid soaking for too long, which may cause excessive corrosion of the electrode surface or excessive volatilization of the solvent.
[0041] The immersion temperature can be adjusted according to the properties of the solvent and the electroplating conditions. Appropriate temperature helps to speed up the penetration and dissolution of the solvent and improve the effect of removing impurities. However, too high a temperature may accelerate the volatilization of the solvent and the corrosion of the electrode, so it needs to be carefully controlled.
[0042] During the soaking process, the solvent can be stirred appropriately to promote the dissolution and removal of impurities, but the stirring speed should be moderate to avoid excessive eddy currents or bubbles that may damage the electrode surface.
[0043] After immersion, the working electrode should be thoroughly cleaned and dried to remove residual solvent and moisture. The magnesium or magnesium alloy material can then be further processed and handled, such as cutting, curling, packaging, etc., to meet different application requirements.
[0044] In summary, the step of soaking the working electrode in an organic electrolyte solvent after electroplating deposition is an important step in optimizing the preparation process of magnesium or magnesium alloy materials. The quality and performance of magnesium or magnesium alloy materials can be significantly improved through reasonable soaking conditions and subsequent treatment.
[0045] In a preferred embodiment, the working electrode, the reference electrode and the counter electrode are pretreated before being immersed in an organic electrolyte including magnesium ions; the pretreatment includes: grinding, cleaning, polishing, scrubbing and drying the electrodes, namely the working electrode, the reference electrode and the counter electrode, in turn to remove impurities on the electrode surface.
[0046] The main purpose of pretreatment is to remove impurities, oxide layers, oil stains, etc. that may exist on the electrode surface to improve the conductivity, flatness and surface activity of the electrode, which is conducive to the uniform deposition of magnesium ions and the close adhesion of the coating.
[0047] Grinding: Use appropriate sandpaper or grinding tools to grind the electrode surface to remove rough parts, scratches and larger impurity particles on the surface. During the grinding process, pay attention to uniform force to avoid excessive wear of the electrode substrate.
[0048] Cleaning: Place the polished electrode in a cleaning solution (such as deionized water, dilute acid solution or organic solvent, etc.) and remove dust, oil and other impurities on the surface by soaking, rinsing or ultrasonic cleaning. The choice of cleaning solution should be determined according to the electrode material and the nature of the surface contaminants.
[0049] Polishing: Use polishing paste or polishing cloth to polish the electrode surface to further smooth the surface and remove tiny scratches and uneven parts caused by the grinding process. After polishing, the electrode surface should present a bright mirror effect.
[0050] Scrub: Use a clean cotton cloth or soft material such as dust-free paper to scrub the electrode surface to remove polishing paste, stains, etc. that may remain during the polishing process. Be careful not to use too much force when scrubbing to avoid scratching the electrode surface.
[0051] Drying: Place the cleaned electrode in a dryer or use hot air to dry it to ensure that there is no moisture left on the electrode surface. Avoid high temperature baking during the drying process to prevent deformation or damage to the electrode material.
[0052] Removing the oxide layer and impurities on the electrode surface through pretreatment can improve the conductivity of the electrode and reduce the resistance loss during the electroplating process. In addition, a smooth and clean electrode surface is conducive to the uniform deposition of magnesium ions and the tight adhesion of the coating, reducing the risk of coating peeling or cracking. At the same time, pretreatment can remove microscopic defects and impurity particles on the electrode surface, thereby reducing the defects and impurity content in the coating and improving the uniformity, density and corrosion resistance of the coating.
[0053] In summary, pretreatment of the working electrode, reference electrode and counter electrode is an indispensable and important step before electroplating deposition. Through reasonable pretreatment process and condition control, the cleanliness and flatness of the electrode surface can be ensured to meet the electroplating requirements, laying a solid foundation for obtaining high-quality magnesium or magnesium alloy materials.
[0054] In a preferred embodiment, the conductive metal includes molybdenum, stainless steel or copper.
[0055] Molybdenum (Mo) is a metal with a high melting point and high hardness, and has good electrical conductivity and corrosion resistance. Molybdenum is particularly stable in high temperature environments. Due to these characteristics of molybdenum, it is often used to make electrode materials, especially in situations where it needs to work in high temperature or highly corrosive environments.
[0056] Stainless Steel (SS) is an alloy steel mainly composed of iron, chromium, nickel and other elements. It has excellent corrosion resistance and good mechanical properties. At the same time, stainless steel also has a certain conductivity. Stainless steel is widely used in various fields, including electrode materials in electrochemical deposition processes. Its corrosion resistance enables stainless steel electrodes to remain stable in a variety of electrolytes.
[0057] Copper (Cu) is a metal with excellent electrical conductivity, second only to silver. In addition, copper has good ductility and plasticity and can be easily processed into various shapes. Copper is one of the commonly used electrode materials in the electroplating industry because it can efficiently transmit current and has a relatively low cost.
[0058] The choice of conductive metal should be determined according to the specific application requirements. Molybdenum, stainless steel and copper are all excellent conductive metal choices, each with unique advantages and application ranges.
[0059] In a preferred embodiment, the organic electrolyte is an ether electrolyte or an ester electrolyte. Ether electrolytes generally have good solubility and stability, can dissolve a variety of electrolyte salts, and can remain stable over a wide voltage range. Ester electrolytes generally have a higher flash point and lower volatility, which means they are relatively safe during use. At the same time, ester electrolytes also have certain solubility and stability. The choice of organic electrolyte should also be determined according to the specific electrochemical process and requirements. Ether electrolytes and ester electrolytes have their own advantages and can perform excellent performance under appropriate conditions.
[0060] Exemplarily, the organic electrolyte is an APC electrolyte, a Mg(TFSI)2-based electrolyte, a MDGM electrolyte or a MTC electrolyte.
[0061] The preparation of the APC electrolyte includes: dissolving phenylmagnesium chloride and aluminum chloride in tetrahydrofuran to obtain the APC electrolyte.
[0062] The preparation of Mg(TFSI)2-based electrolyte includes: first adding 0.4515g of 1-methoxy-2-propylamine (Sigma-Aldrich, 99%) to 2mL of DME (Sigma-Aldrich, anhydrous, 99.5%, inhibitor-free), and then adding Mg(TFSI)2 (Duoduo reagent, 99.5%) while stirring. The final solution is not completely clear but translucent.
[0063] The preparation of the MDGM electrolyte includes: uniformly mixing 10 mL of DME, 10 mL of diethylene glycol dimethyl ether, 4.14 mL of MOEA and 3.2245 g of magnesium trifluoromethanesulfonate to obtain the MDGM electrolyte.
[0064] The preparation of MTC electrolyte includes: first adding 0.5846g of MgCl2 (thermofisher, ultra dry, 99.99%) into 2mL of DME (Sigma-Aldrich, anhydrous, 99.5%, inhibitor-free / macklin 99.5%, with molecular sieves), stirring while adding, and setting the stirring speed to 200~300rpm. After stirring for a period of 3~15min, 0.1904g of Mg(TFSI)2 (Duoduo reagent, 99.5%) is added, stirring while adding, and then the speed is adjusted to 500~600rpm. The solution becomes clear and transparent overnight to obtain MTC electrolyte.
[0065] The following is an analysis and explanation with reference to specific examples.
[0066] Embodiment 1, a low-cost method for preparing magnesium foil, comprising the following steps: Step 1: Cut the purchased high-purity magnesium sheets and molybdenum sheets with a thickness of 0.2 mm into rectangular sheets with a size of 15 mm×10 mm.
[0067] Step 2: Surface treat the cut magnesium sheets and molybdenum sheets by sandpaper of 400 mesh, 600 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh, respectively, then clean with acetone and deionized water to remove impurities on the entire electrode surface, polish with A12O3 powder, scrub with alcohol again, ultrasonically wash for 10 minutes, dry in a vacuum drying oven for 12 hours, and put into a glove box for use.
[0068] Step 3: Assemble the electrodes correctly. The working electrode is a molybdenum sheet, and the reference electrode and the counter electrode are both magnesium sheets. Adjust the electrode spacing to 5 mm, inject 4 mL of APC electrolyte, and adjust the current density to 10 mA / cm at room temperature of 25 °C. 2 , deposition took about 40 minutes, and a magnesium foil with a thickness of approximately 17 μm was deposited on the surface of the working electrode.
[0069] Step 4: After the deposition is completed, remove the working electrode and soak it in a pure electrolyte solvent for 12 hours to remove impurities.
[0070] The microstructure of the magnesium foil obtained in this embodiment was observed. Figure 1 From the SEM image, it can be seen that magnesium is deposited evenly on the working electrode molybdenum, the particles are densely packed, and the particle sizes are almost the same.
[0071] The magnesium foil prepared in this example was subjected to EDS analysis, and the results are shown in Figure 2 From the EDS spectrum, we can see that the red area is magnesium, the black area is the part without vacuum transfer oxidation, and the distribution of magnesium is uniform.
[0072] Example 2: Adjust different current densities to compare deposition uniformity, and control the current density at 2, 3, 4, 5, 6, 7, 8, 9 mA / cm 2 The remaining steps are the same as those in Example 1.
[0073] Observe the microscopic morphology of the magnesium foil deposited under the corresponding current density. The results are shown in Figure 3 As shown, with the increase of current density, polarization increases and the deposition becomes more uniform. From the actual SEM graph, it can be seen that the particle radius of magnesium deposition is decreasing, and the accumulation is dense and uniform. The deposition is most uniform at 10mA / cm².
[0074] In the third embodiment, different temperatures are adjusted to compare the deposition uniformity, and the electrolyte temperature is controlled to be deposited at 35°C, 45°C, 55°C, 65°C, and 75°C. The remaining steps are the same as those in the first embodiment.
[0075] Observe the microstructure of magnesium foil deposited at different temperatures. Figure 4 As shown in the figure, as the temperature increases, the polarization decreases. Theoretically, the number of deposited particles increases. However, at 35°C, the particles are more uniform, and the current density can be increased while the temperature is increased. The polarization can be reduced while the polarization is increased, which can improve the deposition efficiency. Too high a temperature will lead to the decomposition of the electrolyte, the coating will not be tight, and the bonding with the substrate will not be good.
[0076] In the fourth embodiment, different electrode spacings are adjusted to compare the deposition uniformity, and the deposition is performed under the electrode spacing of 5 mm and 10 mm. The remaining steps are the same as those in the first embodiment.
[0077] Observe the microstructure of magnesium foil deposited at different electrode spacings. Figure 5 As shown in the figure, as the electrode spacing increases, the electric field distribution becomes more uniform. At a small electrode spacing, the local electric field distribution is too large, which will lead to preferential deposition and growth in certain areas, resulting in poor quality of the deposited layer. If the electrode spacing is too large, it will reduce concentration polarization, increase the migration path, and also lead to larger deposited particles. At an electrode spacing of 10 mm, the deposited layer is the most uniform, and it can be seen from the SEM and EDS spectra that Mg is deposited particularly uniformly on the working electrode.
[0078] Example 5: Adjusting the influence of working electrodes of different materials on the preparation of magnesium foil, depositing on stainless steel (SS), Cu (copper), Ti (titanium), and the remaining steps are the same as in Example 1.
[0079] Figure 6 The discharge curves for deposition at different current densities show that deposition on Mo has the lowest nucleation overpotential and deposition overpotential, which is more conducive to deposition. It can also be seen that: with the increase of current density, polarization increases.
[0080] Figure 7 This is the first cycle deposition dissolution curve at 1mAh / cm² and 2mA / cm². It can be seen that the Coulomb efficiency of Mg deposition on Mo is the highest, which indirectly explains that Mo has the strongest affinity for magnesium.
[0081] Figure 8 The CV curves of several half-cells show that when the reduction reaction occurs on Mo, the potential moves to the negative direction and becomes more negative, which means that the reaction is easier.
[0082] Fig. 9Figure 2 is the polarization curve of deposition on several metals. The larger the slope, the greater the polarization. Combined with the experimental data analysis, the Tafel slope of deposition on Mo is larger, indicating that by controlling different process conditions, the deposition process on Mo is more uniform.
[0083] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.
Claims
1. A method for preparing magnesium or magnesium alloy material, characterized in that: include: A conductive metal is used as a working electrode, and magnesium or a magnesium alloy is used as a reference electrode and a counter electrode. The working electrode, the reference electrode and the counter electrode are immersed in an organic electrolyte containing magnesium ions, and magnesium or a magnesium alloy material is electroplated and deposited on the surface of the working electrode. The magnesium or magnesium alloy material is a foil or a thin plate.
2. The method for preparing magnesium or magnesium alloy material according to claim 1, characterized in that: The process parameter settings for electroplating deposition include: current density is set to 2~100mA / cm 2 , the temperature of the organic electrolyte including magnesium ions is set to 0~85℃, and the electroplating deposition time is set to 0.01~10h.
3. The method for preparing magnesium or magnesium alloy material according to claim 1, characterized in that: The distance between the working electrode and the counter electrode was set to 5-15 mm.
4. The method for preparing magnesium or magnesium alloy material according to claim 1, characterized in that: After the electroplating deposition is completed, the working electrode is immersed in a solvent of an organic electrolyte to remove impurities on the surface of the working electrode.
5. The method for preparing magnesium or magnesium alloy material according to claim 1, characterized in that: Pretreating the working electrode, the reference electrode and the counter electrode before the working electrode, the reference electrode and the counter electrode are immersed in the organic electrolyte including magnesium ions; The pretreatment includes: grinding, cleaning, polishing, scrubbing and drying the electrodes, namely the working electrode, the reference electrode and the counter electrode, in sequence to remove impurities on the surfaces of the electrodes.
6. The method for preparing magnesium or magnesium alloy material according to claim 1, characterized in that: The conductive metal includes molybdenum, titanium, stainless steel or copper.
7. The method for preparing magnesium or magnesium alloy material according to claim 1, characterized in that: The organic electrolyte is an ether electrolyte or an ester electrolyte.
Citation Information
Patent Citations
Method for preparing aluminum-magnesium alloy membrane through electro-deposition at room temperature
CN103334132A
Method for electro-deposition of magnesium nickel alloy in ionic liquid
CN103422123A
Three-dimensional alloy negative electrode material for magnesium ion battery as well as preparation method and application of three-dimensional alloy negative electrode material
CN117947478A
Process for electrorefining of magnesium by non-aqueous electrolysis
KR1020150062687A
Electrode for magnesium secondary battery and magnesium secondary battery including the same
US20130196236A1